Impacts of the COVID-19 Pandemic on Student Learning and Opportunity Gaps Across the 2020–2021 School Year: A National Survey of Teachers - Namkung, Jessica M.; Goodrich, John Marc; Hebert, Michael; Koziol, Natalie (Frontiers in Education, 2022)
Although many school districts made efforts to provide instruction during the COVID-19 pandemic (including in-person, remote, and blended/hybrid options the length of instruction time and delivery models have varied from district to district. This disruption in education has been projected to result in a significant learning loss, which may be particularly profound for students from disadvantaged backgrounds, leading to widening opportunity gaps. However, there is limited empirical data that can provide important contextual background for understanding the impact of the pandemic on student learning. Therefore, we conducted a national survey with a random sample of 582 elementary school teachers to understand the instructional changes that occurred, the amount of academic content instruction provided to students, and teachers perceptions of the learning supports needed and provided to students during the 2020–2021 school year. Results indicated that most teachers relied on alternative forms of instruction and experienced changes in delivery models but reported low instructional effectiveness. Compared to typical years, teachers reported significant decreases in curriculum coverage; the number of students who received needed interventions, and students who were ready to transition to the next grade level during the 2020–2021 school year. Teachers also reported greater impacts on instruction for students from disadvantaged backgrounds. Follow-up analyses using prior school achievement data corroborated the findings that higher school achievement was associated with smaller impacts on student learning and delivery of instruction.